Program of Positive Psychology Applied to Education on the Psychological Wellbeing of Educational Actors - García-Álvarez, Diego (2020)
In the context of promoting psychological wellbeing in educational settings, the following study is intended a) to determine the impact of a Positive Psychology program such as a character strengths intervention, on the education practitioners’ wellbeing and their pre- and post-modifications; b) to examine the relationship between psychological wellbeing and character strengths after the application of the program. The methodological approach used a pre- and postexploratory model and a correlational analysis. Thus, the study was conducted in two different education practitioner groups working at Uruguayan educative system levels with two sample groups: group A with 34 individuals and group B with 26 individuals. The data recollection instrument used was the Scale of Psychological Wellbeing for Adults [Bieps - A] (Casullo, 2002), and the character strengths sub-scales adapted and validated by Rojas y Feldman (2010), both with extensive evidence on validity and reliability; non parametric hypothesis tests were administered for data analysis as well. The findings showed that there were statistically significant changes in the education practitioners’ wellbeing, both in group A (Z = -4,31, p <0.05) and B (Z = -3,49, p <0.05). Likewise, significant positive correlations were observed between psychological wellbeing and character strengths after the application of the Applied Positive Psychology Educational Program. Further research should be conducted, aimed at analyzing the effects of Positive Psychology interventions on the enhancement of wellbeing in educational settings.